2009
DOI: 10.1002/cmdc.200900257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Characterization of Disila‐AM80 (Disila‐tamibarotene) and Disila‐AM580, Silicon Analogues of the RARα‐Selective Retinoid Agonists AM80 (Tamibarotene) and AM580

Abstract: C/Si switch: Twofold sila‐substitution (C/Si exchange) in the RARα‐selective retinoids 1 a (AM80) and 2 a (AM580) leads to 1 b (disila‐AM80) and 2 b (disila‐AM580), respectively. The chemistry and biology of the C/Si pairs are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…These results prompted us to investigate whether or not other selective, synthetic agonists of other RARs can influence the development of NAFLD. Therefore, we fed 6-week-old C57Bl/6 male wild type (wt) mice a chow diet (13% kcal/fat) or a HFD (45% kcal/fat) for 12 weeks, followed by 4 weeks during which we continued to feed the mice a HFD, but also added either an RARα agonist, AM80 [28], or the RARβ2 agonist AC261066 [16, 20], in the drinking water. We observed increased body weights (bw) in the mice fed a HFD, a HFD+AC261066, and a HFD+AM80 compared to mice fed a chow diet (p < 0.0001) ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results prompted us to investigate whether or not other selective, synthetic agonists of other RARs can influence the development of NAFLD. Therefore, we fed 6-week-old C57Bl/6 male wild type (wt) mice a chow diet (13% kcal/fat) or a HFD (45% kcal/fat) for 12 weeks, followed by 4 weeks during which we continued to feed the mice a HFD, but also added either an RARα agonist, AM80 [28], or the RARβ2 agonist AC261066 [16, 20], in the drinking water. We observed increased body weights (bw) in the mice fed a HFD, a HFD+AC261066, and a HFD+AM80 compared to mice fed a chow diet (p < 0.0001) ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, based on previous research [20], the EC50 of AC261066 for RARβ2 is 7.9 nM, which makes AC261066 selective for RARβ2 over RARα (EC50 = 631 nM) and RAR γ (EC50 = 501 nM). Moreover, Tacke et al [28] showed that 1 nM AM80 was not able to activate RARβ. Taken together, these data indicate that the AM80 and AC261066 concentrations used in the present work should primarily activate the receptors RARα and RARβ2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…13 In recent years, silicon-containing bioactive compounds have been reported. [14][15][16][17][18][19] The incorporation of silicon into organic compounds can improve various biological properties, including selectivity, potency, pharmacokinetics, pharmacodynamics and cell penetration. Indeed, several organosilicon agents have advanced to clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Organosilicon chemistry was initiated in 1846 by Ebelman, and since that time, silicon compounds have attracted attention of the scientific community. In recent years, silicon-containing bioactive compounds have been reported [14][15][16][17][18][19][20][21]. The incorporation of silicon into organic compounds can improve biological properties such as selectivity, potency, penetration, pharmacokinetics, and pharmacodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of silicon into organic compounds can improve biological properties such as selectivity, potency, penetration, pharmacokinetics, and pharmacodynamics. Furthermore, replacement of a carbon atom by a silicon atom in existing drugs is an attractive approach to finding new drug candidates [14][15][16][17][18][19]. Some of organosilicon agents have advanced to clinical studies [20,21].…”
Section: Introductionmentioning
confidence: 99%